Novel 7-oxy-3-(3 ', 4 ', 5 '-trimethoxyphenyl)coumarin substituted zinc(II) phthalocyanines: Synthesis, characterization, photophysical and photochemical properties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2015)
The novel zinc(II) phthalocyanine complexes bearing tetra or octa-[7-oxy-3-(3', 4', 5'-trimethoxyphenyl) coumarin] moieties were synthesized for the first time in this study. These phthalocyanines were characterized by different spectroscopic methods such as FT-IR, H-1 NMR, electronic absorption spectra, MALDI-TOF mass and elemental analyses as well. The photochemical properties such as singlet oxygen generation, photostability and photophysical properties such as fluorescence quantum yields and lifetimes were investigated in N,N-dimethylformamide (DMF) solutions. The effect of the structure (the position and number of the coumarin groups on phthalocyanine framework) of novel phthalocyanines on these properties was also determined in this study.
Keywords: coumarin (2H-chromen-2-one); phthalocyanine; zinc; quantum yield; fluorescence; singlet oxygen; COUMARIN DERIVATIVES; SERIES